Identification of Medicinal Plant Species Utilized by the Community of Tindaki Village, South Parigi District - Risnila Sari; Lestari M.P Alibasyah; Vita Indri Febriani; Aan Febriawan; Musdalifah Nurdin; Lilies (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aims to identify and describe the diversity of medicinal plants utilized by the community of Tindaki Village, South Parigi District, and to document their scientific names, morphological characteristics, plant parts used, and methods of preparation. The research employed a descriptive design with a qualitative approach using exploratory techniques. Data were collected through direct field observations conducted in six hamlets, structured interviews with ten informants consisting of five key informants and five supporting informants, and field documentation. Species identification was carried out through detailed observations of morphological characteristics, including roots, stems, leaves, flowers, and fruits. The identification results were subsequently verified using relevant scientific literature to ensure taxonomic accuracy. The findings revealed a total of 34 medicinal plant species belonging to 23 families and 18 orders. The plant parts most commonly utilized by the community were leaves and rhizomes, followed by fruits, roots, stems, and sap. These plants are traditionally used to treat various health conditions, including fever, cough, diarrhea, diabetes, hypertension, kidney stones, digestive disorders, and skin diseases. In conclusion, the results indicate that Tindaki Village possesses a high diversity of medicinal plants that continue to be actively utilized by the local community. Therefore, sustained conservation and systematic documentation efforts are essential to preserve this valuable ethnobotanical knowledge for future generations.